Abundance and seasonal fluctuations of benthic macroinvertebrates in a swamp lake in Malaysia - Mustafa kamal, A. S.; Mohammad Mohsin, A. K.; Md Yusoff, Fatimah (Malaysian Society of Applied Biology, 1984)
A ten-month study was undertaken to determine the abundance and seasonal fuluctua- tiona of benthic macroinvertebrates in a swamp lake, Paya Bunlor, Pahang. The lake bas a total standing crop of 25,371 animals per m2 representing 17 taxa. The brown water system of the lake has a standing crop of 11,820 animals per m2 representing 9 taxa, while its white water system has a standing crop of 13,551 animals per m2 representing 14 taxa. Gastropods form the major taxanomlc croup In the lake and a gastropod species, Melanoide. sp, form the dominant species. Greater abundance occurs in shallower parts of the lake with dense communities of macrophytes. Abundance is greater during the dry season which begins from February to October with a break In May which is a wet month. The dry season coincides with period of optimal condition for most of the physico-chemical parameters. From the stand point of benthic macrolnvertebrates as a source of fish food, both the white water system and the brown water system are equally suitable for fish culture since the standing crops of both water systems do not differ signiflcantly(p <.05» Fish that feed on gastropods are especially suitable for stocking In this lake. A few species have been reported to habitually or occasionally feed on mollusks including black carp, Mylophamygodon piceu e, Kell, Clariaa batratchua and Temoleh, ProbarbuB jullienl